Modelling aging kinetics of aluminium alloy aa2124 - Tiaw, Wei Ping (School of Materials Engineering, University Malaysia Perlis, 2016)
In this research, an aqueous emulsion technique was used to prepare epoxy spherical porous. Throughout the production of epoxy spherical porous, epoxy emulsion that consists of epoxy, hardener, tapioca powder and water were prepared by using a homogenizer. Further curing process was carried out to solidify the porous epoxy. Tapioca was found to have two functions in the emulsion such of as filler and as an emulsifying promoter. The addition of tapioca as a filler into epoxy resulted a sphere-packing porous and enhanced the compressive properties. The effect of homogenizing temperature was also studied. By conducting the emulsion at low emulsifying temperature (10 oC) enabled to give a fine porous structure with high compressive properties and low porosity as compared to porous obtained from emulsion at room temperature but the sample undergo shrinkage which was not suitable to be chosen as production of porous structure. Next, the effect of tapioca content shows that the incorporation of tapioca powder had increased the emulsion viscosity, enabling fabrication of smaller epoxy particles with lower porosity. Excess of tapioca powder content led to agglomeration whereby it affected the porous formation. Consequently, low compressive strength and compressive modulus were obtained from the epoxy porous with excess tapioca powder content. Based on that, 20 phr filled tapioca porous epoxy was found to be the optimum formulation to produce epoxy porous.